Investigating the photodegradation mechanism and effects of excess iodide on the photostability of all-inorganic lead halide perovskite - Soo, Shawn Zuo Xiang (Nanyang Technological University, 2024)
Perovskite solar cells (PSCs) have risen in popularity following its rapid advancement in performance over the years since its invention in 2009. Hybrid PSCs such as MA/FAPbI3 have exhibited excellent power conversion efficiency (PCE) and good intrinsic stability, but do however suffer greatly from its poor extrinsic stability. Although lacking behind in performance, scientists have gravitated towards the use of all-inorganic PSCs due to its excellent extrinsic stability over its hybrid counterparts, particularly CsPbI3 mainly due to its suitable bandgap (~1.7eV). However, all-inorganic PSCs still suffer from poor phase stability and much research have been carried out to improving intrinsic stability, whereas little attention have been placed on its extrinsic stability, especially its photostability. Herein, we aim to investigate the full photodegradation reaction and mechanism of CsPbI3, as well as to identify the products formed from the photodegradation of the perovskite. When exposed to light for a prolonged duration, we have shown that CsPbI3 perovskite film will undergo photodegradation to form cesium iodide (CsI) crystals and an intermediate product of lead iodide (PbI2), before it undergoes further photodegradation to form lead (Pb0) metal and iodine (I2). With regards to the photodegradation mechanism, we propose that photodegradation is driven by the ion migration of iodide anions (I-), which drives the formation of I2 and more anionic vacancies, ultimately resulting in the formation of Pb0 metal.